Identification and predictors of age-relevant and activity-relevant hop test targets in young athletes after anterior cruciate ligament reconstruction - Schmitt, L. C.; Brunst, C.; Ithurburn, M.; Ilardi, D.; Thomas, S.; Huang, B.; Paterno, M. V. (Journal of Athletic Training, 2022)
Context Performance symmetry between limbs (limb symmetry index [LSI] = 90%) on a battery of single-leg hop tests is recommended to inform return-to-sport (RTS) decisions after anterior cruciate ligament (ACL) reconstruction (ACLR). Achieving current hop test symmetry values has not been associated with future clinical outcomes. The identification of age-relevant and activity-relevant target values to benchmark the hop test performance of young athletes post-ACLR may provide greater specificity and clinical relevance for interpretation of hop test data.